Muscarinic receptor activation determines the effects of store-operated Ca2+-entry on excitability and energy metabolism in pyramidal neurons - Kann, Oliver; Papageorgiou, Ismini E. (Cell calcium, 2012)
In various cell types, depletion of intracellular Ca2+-stores results in store-operated Ca2+-entry (SOCE) across the cellular membrane. However, the effects of SOCE on neuronal membrane excitability and mitochondrial functions in central neurons are not well defined. We investigated such cellular downstream effects in pyramidal neurons of rat organotypic hippocampal slice cultures by applying electrophysiological and fluorescence imaging techniques. We report that SOCE is associated with (i) elevations of Ca2+-concentration in individual neuronal mitochondria ([Ca2+]m). In addition, SOCE can result in (ii) hyperpolarizing neuronal membrane currents, (iii) increase in extracellular K+-concentration ([K+]o), (iv) mitochondrial membrane depolarization, and (v) changes in intracellular redox state (NAD(P)H and FAD fluorescence), the latter reflecting responses of energy metabolism. These additional downstream effects of SOCE required concomitant muscarinic receptor activation by carbachol or acetylcholine, and were suppressed by agonist washout or application of antagonist, atropine. We conclude that muscarinic receptor activation determines the downstream effects of SOCE on neuronal membrane excitability and energy metabolism. This mechanism might have significant impact on information processing and neurometabolic coupling in central neurons.